Comparison of dietary and plasma phospholipid fatty acids between normal weight and overweight black South Africans according to metabolic health: The PURE study. (July 2020) - Ojwang, A.A.; Smuts, C.M.; Zec, M.; Wentzel-Viljoen, E.; Kruger, I.M.; Kruger, H.S.
Highlights: First published study of dietary fatty acids and plasma phospholipid fatty acids in black African's. Plasma phospholipid fatty acids compared between middle-aged black South Africans. Specific plasma phospholipid fatty acids, both saturated and monounsaturated as well estimated desaturase activities may be associated with abnormal metabolic health in black Africans. Plasma phospholipid fatty acids levels of metabolically healthy and unhealthy phenotypes of black Africans are different from results documented in other epidemiological studies. Abstract: Background: Information regarding circulating fatty acids (FA) in association with metabolic health in black Africans is scarce, while the usefulness of circulating FAs as biomarkers of dietary fat intake and predictors for medical conditions is increasing. Objective: We compared eleven dietary and the levels of 26 plasma phospholipid FAs in metabolically healthy and unhealthy phenotypes in black South African adults. Methods: Adults from the South African arm of the Prospective Urban and Rural Epidemiology study baseline ( n  = 711) were categorised into four groups, namely normal weight without metabolic syndrome (MetS) (MHNW), normal weight with MetS (MUNW), metabolically healthy overweight/obese (MHO) and metabolically unhealthy overweight/obese (MUO). Dietary and plasma phospholipid FAs were measured by a quantitative food frequency questionnaire and gas chromatography-tandem mass spectrometry, respectively. We compared dietary FAs, plasma phospholipid FAs, and estimated desaturase activity between the metabolic status groups using ANCOVA adjusted for age and energy intake. Results: MetS was diagnosed in 35% of the participants. After adjustment for age and total energy intake, in comparison to the MHNW reference group, saturated dietary FAs (C14:0 to C18:0) and alpha-linolenic acid intakes were higher in both overweight/obese groups (MHO and MUO), while linoleic acid intakes were higher in the MUO group only. Plasma levels of most saturated FAs (C18:0 to C22:0) and PUFAs were higher, whereas selected MUFAs, palmitic acid, and estimated desaturase activities were lower in the overweight/obese groups. Conclusions: The overweight groups generally had higher fat intakes than normal-weight groups, but lower plasma levels of palmitic, palmitoleic, oleic, cis-vaccenic and estimated desaturase activities. Therefore, in this population, lower plasma levels of palmitic, palmitoleic, oleic, and cis-vaccenic acids and decreased estimated desaturase activities may be biomarkers of abnormal metabolic health in overweight/obese study participants.